Estrogens and the G protein-coupled estrogen receptor in prostate cancer: angels or demons? - Figueira, Marília Isabel Neto (2023)
Prostate cancer (PCa) is the second most frequent type of cancer among men, with an increasing incidence worldwide. PCa is highly regulated by hormones, with androgens playing a crucial role in its development and progression. However, also estrogens are accepted to influence PCa. In fact, estrogens were used in PCa treatment for decades, after the pioneer work of Huggins and Hodges demonstrating that PCa is a hormone-sensitive cancer, stimulated by androgenic activity and inhibited by suppression of androgens levels or estrogens administration. Nevertheless, despite the effectiveness of estrogens administration in delaying the progression of metastatic PCa, this therapy was discontinued because of the adverse side effects. Over the years, a vast number of studies were performed with the aim of deciphering the role of estrogens in PCa and find new estrogen-based alternatives for PCa treatment without the adverse effects. However, a contradiction in the estrogens actions remains evident in the literature until now. Many studies have pointed out estrogens as causative agents of PCa, contributing to its development and progression. Though, also a panoply of reports defended estrogens as protective against PCa, suppressing tumor growth, inducing apoptosis and inhibiting metastization, in line with their efficacy as therapeutic agents. This dual activity was associated with the diversity of receptors activated by estrogens, with the pro-carcinogenic actions associated with the activation of the estrogen receptor α (ERα), whereas anti-carcinogenic effects are linked to ERβ activation. Moreover, the discovery of G protein-coupled estrogen receptor (GPER) increased the complexity of mechanisms orchestrating estrogens actions. GPER is a membrane-bound ER that mediates the rapid, non-genomic effects of estrogens by mobilizing intracellular calcium and activating several signaling pathways. A substantial amount of evidence in different cancer types has been describing the anti-tumorigenic effects of GPER suppressing tumor growth and progression. A research area with increasing interest is the determination of the anti-carcinogenic actions of phytoestrogens, strengthened by the evidence of the lower incidence of PCa in Eastern countries, which typically have high consumption of these compounds in a consequence of plant-enriched diets. Furthermore, the mechanism of action of some of these compounds in PCa cells has been shown to require GPER activation. The present thesis aimed to answer some of the existent questions on the estrogens and GPER actions in PCa cells, which would lay the foundations for the development of new and safe estrogen-based therapies. First, it was investigated the action of estrogens as regulators of apoptosis and proliferation in prostate cells in the interplay with the SCF/c-KIT system, a set of ligand and receptor highly involved in carcinogenesis and a target of steroid hormones. Herein, it was demonstrated that E2 down-regulated the expression of the SCF/c-KIT system both in human PCa cell lines and rat prostate in vivo, which was accompanied by the effects of E2 suppressing proliferation and inducing apoptosis in rat prostates. These results supported the protective role of estrogens against PCa. Considering the promising results in other types of cancer, it was determined the effect of GPER activation in PCa cells covering several cancer hallmarks, from cell fate to metabolic reprogramming. It was found that GPER is highly expressed in PCa compared to benign prostatic hyperplasia (BPH) cases. Furthermore, GPER immunoreactivity was inversely correlated with PSA levels. GPER protein levels also were higher in neoplastic LNCaP cells than in the non-neoplastic PNT1A cells. Nevertheless, castrate-resistant PCa (CRPC) cells displayed reduced expression of GPER compared to the androgen-responsive cell line, supporting that GPER protein levels could be modulated by androgens. GPER was found to be localized at the cell membrane, endoplasmic reticulum and, residually, in the nucleus of prostate cells and this subcellular localization was altered by the GPER-specific agonist G1. G1-treatment showed a multiplicity of beneficial effects in PCa, targeting a panoply of cancer hallmarks. It reduced PCa cells viability and proliferation, arresting cell cycle and increasing apoptosis. It was also able to reduced migration and invasion, concomitantly with epithelial-mesenchymal transition (EMT) attenuation, depending on the cell line. Moreover, GPER activation by G1 increased energy metabolism and oxidative stress in PCa cells. Finally, it was evaluated how natural compounds, such as diosgenin, can influence the behavior of PCa in the interplay with GPER. Diosgenin diminished the viability of androgen-responsive and CRPC cells, without affecting the viability of non-neoplastic PNT1A cells. Moreover, the compound induced apoptosis and modulated glycolytic metabolism of PCa cells. The effects of diosgenin were enhanced when combined with G1, supported by the ability of diosgenin to augment the expression levels of GPER. Furthermore, GPER knockdown by a siRNA approach abrogated diosgenin effects inducing apoptosis of PCa cells, which implicates this receptor in the diosgenin mechanism of action. Globally, the findings of this thesis support the protective role of estrogens in PCa, disclosing new molecular targets and cellular processes. Moreover, it provides valuable information to find new therapeutic options, namely, estrogen-like, to deaccelerate the progression of disease and improve the survival of PCa patients.